Monetary policy and inflation dynamics in Ghana - BORTEY, Isaac Newton (KDI School, 2015)
The study sought to explore the relationship that exists between monetary policy and inflation in Ghana by examining the extent to which inflationary pressures can be attributable to monetary policies. Stylized facts and data on the Ghanaian economy show that, money supply and inflation has shared a similar trend for most years. Quarterly data ranging from 1990q1 – 2013q4 on money supply, CPI and other determinants of inflation were used in the study. Employing impulse response function and variance decomposition in a VAR and VECM model, the paper found the existence of a long-run relationship between inflation and the other variables, also the variations in inflation is the results of money supply, the nominal exchange rate, and shocks to inflation itself. The empirical findings also show that response of inflation to a shock persists for over two years (six quarters), with the adjustment from disequilibrium fairly slow.
Thesis(Master) --KDI School:Master of Development Policy,2015